Relapse-independent multiple sclerosis progression under natalizumab. Issue 4 (9th October 2021) - Graf, Jonas; Leussink, Verena I; Soncin, Giulia; Lepka, Klaudia; Meinl, Ingrid; Kümpfel, Tania; Meuth, Sven G; Hartung, Hans-Peter; Havla, Joachim; Aktas, Orhan; Albrecht, Philipp
Abstract: The objective of this study was to investigate confirmed progression independent of relapse activity in relapsing-remitting multiple sclerosis patients under long-term natalizumab treatment. We performed a retrospective, cross-sectional study of clinical data captured between 1994 and 2019 at two German multiple sclerosis tertiary referral centres. Data files of all relapsing-remitting multiple sclerosis patients treated with natalizumab for ≥24 months were analysed. Confirmed progression independent of relapse activity was defined as ≥12 week confirmed disability progression on a roving Expanded Disability Status Scale reference score by 1 point in patients with an Expanded Disability Status Scale score ≤3 or 0.5 in patients with an Expanded Disability Status Scale score ≥3.5 in the absence of a relapse. Cox proportional hazard models were used to analyse the probability of developing confirmed progression independent of relapse activity depending on both disease and natalizumab treatment duration. Among the 184 patients identified, 44 (24%) developed confirmed progression independent of relapse activity under natalizumab irrespective of the Expanded Disability Status Scale score at natalizumab onset. Time to confirmed progression independent of relapse activity was not affected by Expanded Disability Status Scale at natalizumab onset (categorized by Expanded Disability Status Scale score ≤3.5 versus >3.5) nor by duration of disease nor by duration of therapy. Confirmed progression independent of relapse activity occurred earlier in the disease course in patients with an earlier natalizumab therapy onset with regard to disease duration. A stepwise forward regression analysis revealed disease duration as the main factor for confirmed progression independent of relapse activity development ( P = 0.005). Taken together, confirmed progression independent of relapse activity occurs in a substantial proportion of patients on long-term natalizumab treatment and independent of Expanded Disability Status Scale score at natalizumab onset. Our findings suggest that patients who are initiated on natalizumab early during disease course, usually in order to treat an aggressive clinical phenotype, have a higher risk of early confirmed progression independent of relapse activity. Abstract : Graf et al. aimed to assess the relevance of relapse-independent disease progression in relapsing remitting multiple sclerosis patients under long-term natalizumab treatment. In this study, more than 20% of multiple sclerosis patients developed relapse-independent disease progression, mostly linked to a more active disease course prior to natalizumab onset. Graphical Abstract: